The Making of an Imperial Polity Civility and America in the Jacobean Metropolis - Working, Lauren (Social Sciences, 2020)
Bringing to life the interaction between America, its peoples, and statesmen in early seventeenth-century England, this book offers new perspectives on Jacobean tastes and political culture, confronting the histories of colonialism and domestic political development. This title is also available as Open Access.